Penerapan PSAK No. 102 Atas Transaksi Murabahah: Studi Kasus BMT - Ahmad Jarot; Desi Ratna Sari; Hanifatun Nisa; Ersi Sisdianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the accounting treatment of murabahah (recognition, measurement, presentation and disclosure) in accordance with PSAK no. 102. BMT in 13 population was studied. The descriptive analysis with qualitative and quantitative approaches wasused to deploythe questionnaires to respondents. The study showed that the accounting treatment of murabahah in BMT is not all adopted PSAK no. 102 properly. The average value of the percentage only reached 68.4%. There are weaknesses in the educational background of the respondents were limited to the knowledge of transaction records BMT.